Diagnostic Radiology : Recent Advances and Applied Physics in Imaging - Gupta, Arun Kumar; Chowdhury, Veena; Khandelwal, Niranjan (New Delhi : Jaypee Brothers Medical Publishers, 2013)
Fully updated, second edition providing radiologists with all the recent technological advances in diagnostic radiology. Covers all the key aspects of the imaging - ultrasound, computed tomography, magnetic resonance imaging, radiography and interventional radiography, and contrast media.
Brinda a los radiólogos todos los avances tecnológicos recientes en radiología diagnóstica. Cubre todos los aspectos clave de las imágenes: ultrasonido, tomografía computarizada, resonancia magnética, radiografía y radiografía intervencionista, y medios de contraste.
SECTION 1. Advances in ultrasound imaging SECTION 2. Advances in computed tomagraphy SECTION 3. Advances in magnetic resonance imaging SECTION 4. Advances in radiology SECTION 5. Update in contrast media SECTION 6. Miscellaneous
Keywords: IMAGEN POR ULTRASONIDO; TOMOGRAFÍA COMPUTARIZADA; IMAGEN DE RESONANCIA MAGNÉTICA